1999
DOI: 10.1046/j.1440-0979.1999.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing nurse–patient interaction in the acute psychiatric setting: An exploratory investigation

Abstract: Nurse-patient interaction in acute psychiatric in-patient facilities has been the subject of much discussion in the literature and remains a contentious issue. How and why nurses interact with patients in the acute care setting requires definition within the current dynamic environment of mental health service provision. Factors which impact on the manner in which nurses care for patients also require investigation. This article presents the findings of a collaborative research study that investigates factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 13 publications
(11 reference statements)
8
43
2
Order By: Relevance
“…The hard tasks of nursing (routine tasks, long shift hours, successively working shifts and excessive paperwork), lack of welfare facilities (sleeping quarters and private rooms in wards) for nurses and burn out are other barriers emphasized by nurses. Cleary et al. (1999) found the same barriers as in the present study, in which nurses considered lack of time, fatigue and heavy workload as factors blocking communication between nurses and clients.…”
Section: Discussionsupporting
confidence: 81%
“…The hard tasks of nursing (routine tasks, long shift hours, successively working shifts and excessive paperwork), lack of welfare facilities (sleeping quarters and private rooms in wards) for nurses and burn out are other barriers emphasized by nurses. Cleary et al. (1999) found the same barriers as in the present study, in which nurses considered lack of time, fatigue and heavy workload as factors blocking communication between nurses and clients.…”
Section: Discussionsupporting
confidence: 81%
“…[41] This finding is consistent with other studies that showed lack of time, heavy workload, work in extra shifts, and fatigue in nurses hindered nurse–patient communication. [442] In contrast, the study of Chan et al . showed that nurses with integrating communication within the routines that they tend to do, in practice prove that not only extra time is not needed to communicate with the patients but also good communication is possible without wasting their time.…”
Section: Discussionmentioning
confidence: 96%
“…(2005) found that although nurses did perceive the therapeutic role to be their most important role, it was a role they were often prevented from performing. As Cleary et al . (1999) states, the nursing ward is structured so that ‘something always comes up’ to replace nurse–patient interaction.…”
Section: Introduction/backgroundmentioning
confidence: 87%